Automated dispensing cabinets and their impact on the rate of omitted and delayed doses: A systematic review - Emma Jeffrey; Melanie Dalby; Áine Walsh; Kit Lai (Elsevier, 2024)
Use of automated dispensing cabinets (ADCs) is increasing in hospital settings. ADCs bring various potential benefits, among which are improvements to patient safety and reduction of medication errors. A core function of ADCs is to prevent medication stock outs by triggering an order when stock is reaching low levels. A quantifiable patient safety measure is the occurrence of omitted or delayed doses, which can range in severity from being negligible, to potentially fatal. The purpose of this review is to identify and synthesise the existing evidence regarding the impact of ADCs situated in secondary and tertiary care inpatient settings, on the rate of omitted and delayed doses as a specific subsection of medication errors. In April 2024 searches were conducted in Embase, PubMed and CINAHL, with additional articles discovered through citation searching and from colleagues. A total of 375 articles were returned from the search. Nine articles met the inclusion criteria. The most common reason for exclusion was due to lack of relevance. The included papers were focused on centres which had implemented six or fewer ADCs. The studies mostly presented findings which suggest ADCs have a positive impact on the rate of omitted or delayed doses, although crucially only two papers correlated missed doses due to unavailability of medications The studies highlighted other factors which should be considered prior to the implementation of ADCs. Factors included staffing requirement, type of stock held in the cabinets, and interoperability with other systems. Studies only reported omitted or missed doses, none reported results on delayed doses. It is widely accepted that ADCs can prevent medication unavailability but there is a paucity of evidence linking the improved availability of medications through the utilisation of ADCs with the perceived impact on missed or delayed doses. Further multi-centre studies are needed to determine this causality.